Tindak Tutur Imperatif Guru dalam Pembelajaran di SD Negeri Aik Kangkung Kecamatan Sekongkang - Fitria Sari; Mahsun; Burhanuddin (Jurnal LENTERA: Jurnal Studi Pendidikan, 2022)
This study aims to describe the meaning of imperative speech acts in the interaction of teachers and students in learning, and to describe the tendency of imperative speech acts that occur and are often used by teachers at SD Negeri Aik Kangkung Kec. Sekongkang. This type of research uses the descriptive analysis method, where the researcher analyzes the data associated with the implementation of imperative pragmatics. The data obtained such as the results of observations, observations, document analysis, field notes compiled by researchers, and the results of the data are presented in the form of narrative descriptions. From the research results obtained 1). There are five forms of imperative speech found in the teacher's Imperative speech act research in Learning at SD Negeri Aik Kangkung, Sekongkang District, both in the classroom and outside the classroom as many as five forms of speech, namely ordinary orders or orders, orders or subtle orders. , utterances of command requests, utterances of orders of invitation and hope, and utterances of prohibitions. The total amount of data found by the researcher in the imperative speech research after the data triangulation process is as many as 79 utterances consisting of 31 utterances of ordinary orders or orders, 20 utterances of subtle orders, 9 utterances of request orders, 11 utterances of invitation and wish orders, and 8 utterances of prohibition orders. . The dominant form of imperative speech used by teachers both in the classroom and outside the classroom is the usual command or order speech which is found as many as 31 utterances. 2). The most dominant form of speech acts used by teachers in learning at SD Negeri Aik Kangkung is the usual order or errand that is found in as many as 31 utterances or 39.24%